2011
DOI: 10.4061/2011/694817
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Modifying Agents in theIn VitroProduction of Bovine Embryos

Abstract: The low efficiency observed in cloning by nuclear transfer is related to an aberrant gene expression following errors in epigenetic reprogramming. Recent studies have focused on further understanding of the modifications that take place in the chromatin of embryos during the preimplantation period, through the use of chromatin modifying agents. The goal of these studies is to identify the factors involved in nuclear reprogramming and to adjust in vitro manipulations in order to better mimic in vivo conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 112 publications
0
6
0
2
Order By: Relevance
“…100 The gene expression patterns in the ICM and TE of bovine blastocysts were consistent with the histone modification patterns on the promoter of selected genes, including POU5F1 (OCT4), NANOG, INFT, GAPDH, SLC2A3, and IGF1. 100 Only few studies reported effects of IVC on chromatin configuration changes in bovine embryos, and alterations in histone modifications in in vitro produced embryos 101 and in parthenotes 102 have been described. A recent study suggested that cloned bovine embryos were reprogrammed with histone modifications similar to that of IVF embryos, both IVF-derived and cloned embryos showed a homogeneous distribution of histone modifications in morulae and blastocysts.…”
Section: Embryo Culturementioning
confidence: 99%
“…100 The gene expression patterns in the ICM and TE of bovine blastocysts were consistent with the histone modification patterns on the promoter of selected genes, including POU5F1 (OCT4), NANOG, INFT, GAPDH, SLC2A3, and IGF1. 100 Only few studies reported effects of IVC on chromatin configuration changes in bovine embryos, and alterations in histone modifications in in vitro produced embryos 101 and in parthenotes 102 have been described. A recent study suggested that cloned bovine embryos were reprogrammed with histone modifications similar to that of IVF embryos, both IVF-derived and cloned embryos showed a homogeneous distribution of histone modifications in morulae and blastocysts.…”
Section: Embryo Culturementioning
confidence: 99%
“…Reprogramming of the donor nucleus by the recipient oocyte is crucial during early development of the reconstructed embryo (Hiendleder et al, 2004), but the mechanism remains unclear. Generally, the efficiency of SCNT is low (Wilmut et al, 2002) and a number of studies have focused on improving the efficiency of bovine cloning (Betthauser et al, 2006;Fujii et al, 2010;Monteiro et al, 2010). Our previous study showed that usage of donor cells and enucleated oocytes from an individual female bovine, termed "autologous SCNT", improved the cloning efficiency and resulted in a decrease in reprogramming deficiencies compared with the "allogeneic SCNT" procedure, which utilizes donor cells and enucleated oocytes from different females (Yang et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…An increase of up to five fold in the success rate of mouse cloning was observed. Since then, a flurry of papers were published showing the effect of HDACis on SCNT in different species (MONTEIRO et al, 2010). The results are promising, but in some species such as bovine, remains highly controversial (AKAGI et al, 2013;GALLI et al, 2014).…”
Section: Epigenetic Mechanisms Of Natural Reprogramming Versus Cloningmentioning
confidence: 99%